Collaborative Governance dalam Pelaksanaan Qanun Aceh Nomor 8 Tahun 2018 tentang Fasilitasi Pencegahan Penyalahgunaan Narkotika Studi : BNNK Lhokseumawe dengan Pemerintah Kabupaten Aceh Utara - Hamidi, Muslem; Hafni, Nur; Candrasari, Ratri; Hasyem, Muhammad (Jurnal Transparansi Publik (JTP), 2024)
This research examines the circulation of narcotics in Aceh, which is increasingly very worrying. Narcotics in Aceh are now a real threat that must be considered by all components of society. The location of Aceh Province, which is in the Malacca Strait, makes Aceh a strategic area. so this is a serious threat to Aceh Province, especially related to smuggling and illicit narcotics. This study aims to find out how collaborative governance is used in carrying out the implementation of Aceh Qanun Number 8 of 2018 concerning the facilitation of the prevention of narcotics abuse in North Aceh. In this study, we used qualitative research methods with a descriptive approach to gain a comprehensive understanding. The results of the research show that the dynamics of collaboration in preventing narcotics abuse in the North Aceh district are not good enough because there is no collaboration, so the socialization function that should be carried out together is not working and there is no joint discussion between parties to start a collaboration plan, so the goals of cooperation mandated in the qanun are not achieved. The process of promoting collaboration was null because there was no collaboration, so several parties urged the North Aceh district government to immediately take steps to realize this collaboration